ANTIBACTERIAL, ANTIOXIDANT ACTIVITIES AND ASSOCIATION AMONG PLANT GROWTH RELATED TRAITS OF LEPIDIUM DRABA - Ali, Q; Khalil, R; Nadeem, M; Azhar, MM; Hafeez, MM; Malik, A (Biological and Clinical Sciences Research Journal, 2020)
The Lepidium draba or white tope also known as hoary cress belongs to family Brassicaceae, has been known as one of the perennial herbs which grow normally from seeds and also produced horizontal long creeping roots. It normally grows as a weed plant in farm fields. The present study was conducted to find out the antibacterial and antioxidant activities along with the plant traits of Lepidium draba. The shoot, root and inflorescence extracts were taken through using ethanol, water and n-hexan as extraction solvents. It was found from our studies that the plant extracts were heaving alkaloids, saponins, flavonoids, coumarins, anthocyans, quinons, steroids, sterols and terpenoids as potential phenolic compounds. The bacterial strains including Escherichia coli, Klebsiella pneumonia and Staphylococcus aureus were cultured to access the antibacterial activities of plant extracts. The higher antibacterial activity was reported from n-hexan extract which indicate that the n-hexan extract may be used for extracting phytochemicals to be used as potential antibacterial biomedicines. The water extract showed higher antioxidant activities as compared with ethanol and n-hexan extracts which indicated that the use of water extract may be as a useful antioxidant under stress conditions, may also have anticancer activities. The lower coefficient of variation was recorded for all of the studied traits which indicated the consistency of results and reliability of selecting plants from various locations. There was significant and positive correlation among plant height with inflorescence weight, leaf area and leaf length, the inflorescence weight showed positive correlation with plant height, lea length and leaf area. There was higher contribution of plant height while leaf area contributed lower and negatively towards fresh plant weight. We have concluded from our study that the Lepidium draba plant extract showed antibacterial and antioxidant activities through using ethanol, water and n-hexan as extraction solvents. The significant correlation and regression associations indicated that the plants can tolerate harsh environmental conditions.